PROFIL DAN HIRARKI ULAMA - Rahmad Salahuddin Tri Putra (Universitas Muhammadiyah Sidoarjo, 2015)
The role of Moslem theologians throughout Islamic history had occupied a strategic position – narration Nikkie R Kiddie was termed powerful – and had a great influence in shaping the Islamic society. The religious capacity of Moslem theologians was also recognized officially recognized by the authorities as the mosque trustees, Master/ Mudarris, Mufti and Judge, besides having the privileges from the authorities to teach at mosques, primary schools, and having responsibility towards the quality of education in the community. The Moslem theologians authority was not only in matters of law and education, but also contemporary issues whose capabilities were not specialized and undifferentiated. Keddie divided two groups of Moslem theologians namely; Sunni (orthodox) from religious scholars and legal experts (jurists); andShi’ah authority (sectarian moslem theologians) from a cousin of the prophet Muhammad and his sons - Ali and his descendants considered as the rightful leader, to the Muslim community